An??lise de Desempenho de Redes de Teleprote????o de Sistemas de Distribui????o de Energia utilizando Simula????o e Emula????o - Santos , Jos?? Rodrigo dos (2022)
The growing need for more reliable, efficient, and resilient power grids has become indispensable with recent technological development. Technological evolution and industrial growth generate increasing demand for electricity. As a consequence, it also creates a continuous need for expansion in energy distribution services. However, this expansion raises several questions, whether in the private or government sectors, about management, security, and costs for their technological development. In this way, we understand that the use of telecommunications, linked to electrical networks for the implementation of an efficient teleprotection service, is crucial to boost the development and operation of the electrical network system. Currently, several communications technologies have been applied to seek a more efficient solution in using teleprotection linked to electrical networks. In this work, we will approach different aspects of some of these technologies to address the problem of managing teleprotection services in electrical networks. Among these technologies, we can mention some examples such as Flex LSP from CISCO, Hard Pipe from Huawei, MPLS/IP packet switching protocol and GNS3 software. A framework of scenarios will be presented that were developed from the CEMIG project to study teleprotection networks linked to electrical networks, in such a way that we make use of packet switching technology, involving CISCO and Huawei equipment in the construction of physical scenarios for tests. In this way, we compare the results of a physical scenario with a software scenario. The software is a teleprotection network simulator, representing the physical teleprotection equipment and relays of the electrical network. In this dissertation, we defend the hypothesis that the use of a simulator system, capable of integrating telecommunications networks with energy distribution networks, will present gains in technological development and the economy of project resources.